ADAPTASI PERTANIAN PENDUDUK DI KAWASAN KONSERVASI (Studi Tentang Perambahan Laban Kasus Tanaman Kulit Manis di Taman Nasional Kerinci Seblat, Jambi, Sumatera) - Ary Wahyono (Jurnal Kependudukan Indonesia, 2007)
The aim of this study is to give an understanding on the behavior of forest intruders cultivating commercial plants in Buffer Zone National Park Kerinci Seblat. The research results can be summarised as follows: The Cinnamon mixed garden (Ladang tumpangsari system) is a form of the agricultural adaptation developed by most farmers to meet life necessities. The flexibility of harvesting system enables the farmers to develop Cinnamon mix garden. These plants can be harvested any time that is suitable to the farmer. Cinnamon tree can function as savings. They can also be harvested to meet special needs (travel, marriage, education fee, pilgrimage, etc). The development of Cinnamon mixed gardens has caused farmers to take into account the fertility of the land. Therefore, they have cleared away another location to cultivate vegetable anew. The farmer has two strategies: the firSt that they clear away the forest area and the second is to clear away the Cinnamon bark plant cultivation area. However, viewed from an ownership aspect and the age variation of Cinnamon bark plant, it can be said that farmers in Kerinci do not poses pennanent shifting cultivation pattern. The ownership pattern of Cinnamon cultivation is not identical with the ownership of wet paddy field cultivation, which is still controlled by customary laws (by turns through matrilineal channel). Hence, the cultivation system of Cinnamon is no longer controlled by customary laws but became private property. Compared to wet paddy filed the ownership pattern, Cinnamon trees utilization rights are unlimited and no institution has control as in case of wet paddy filed. This research paper used primary data based on reaserch conducted in 1999. The analysis unit is Cinammon farmers. Qualitative and quantitave approach is used in this research paper.